Energies of Cuprous Oxide Nanofilms and Annealing Temperature Effect on Structural and Dispersion Properties using Fuzzy Logic - Zgair , Inass Abdulah; Al-Ogaili, Abdulazeez O. Mousa; Abass, Khalid Haneen (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Solar cell fabrications need films with nanostructure without defects, which can achieve at a quantum dot or fine grain size. The structural, optical characteristics, and energies of the films of as-grown and annealed Cuprous Oxide (Cu2O) were deposited onto glass substrates via the thermal evaporation technique were studied. The average crystal size of the nanofilms was increased from 12 nm to 16 nm after annealing at 200 ºC, while the dislocation density was decreased. The consequence displays that the fabricated films had transmittance at UV- region of more than 98% and the shift of absorption edge was towards a longer wavelength after the annealing process. The value of the direct band gap of as-deposited Cu2O thin film was 2.57 eV and it decreased to be 2.15 eV for annealed films. Volume Loss Energy Function and Surface Loss Energy Function and dispersion parameters such as single oscillator energy (Eo), Dispersion energy (Ed), static refractive index (n (0)), and Moments (M-1 and M-3) were studied to determine the suitable applications such as solar cell, optoelectronic and optical devices, or in communications using Fuzzy Logic.